Tinjauan Teologis dan Perpektif Budaya tentang Berkat Keturunan dan Kemandulan - Jepri Hutabarat (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2022)
The birth of a child is a great joy for a family. Generally, husband and wife are more hopeful about having children than any other desire. Even though many couples delay having children, in the end, the presence of a child will bring great satisfaction to them. Infertility is an essential issue for married couples when it comes to God's blessing on the promise of offspring. How does the Bible answer this? Is infertility the work of God and his will? The method used in this article is the research library method using sources from literature, while the outlines that are described are: discussing the promise of descent, the biblical perspective on infertility, cultural perspectives on infertility, a prayer asking for offspring, understanding the theological meaning of infertility, and finally, that infertility cannot be viewed as a curse or punishment.